(untitled) (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
The research was conducted to analyze the effect of product quality, price and E-WOM on Shopee consumer purchasing decisions partially. The research method applied is quantitative. Sampling using purposive sampling technique. The number of samples is calculated using the unknown population formula. The number of samples obtained was 100 respondents. Hypothesis testing is done with regression analysis using SPSS. 27. The results of the study prove that product quality (X1) partially has a negative and significant effect on purchasing decisions (Y) of Shopee consumers with a significance value of 0.000 <0.05; price (X2) partially has a positive and significant effect on the purchasing decision variable (Y) of shopee consumers with a significant value of 0.000 <0.05 and E-WOM (X3) partially has a positive and significant effect on purchasing decisions (Y) of shopee consumers with a significant value of 0.000 <0.05. The results also prove that product quality, price and E-WOM are able to explain as much as 53% of the variability in shopee consumer purchasing decisions, while 47% is explained by other variables outside the research model.